EVALUATION OF POSSIBLE ANTICONVULSANT EFFECT OF ALSTONIA SCHOLARIS (LINN.) R. BR. EXTRACTS ON EPILEPSY MODELS - Quazi, Jawed ALI (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: In this study, the effects of ethanolic extract of Alstonia scholaris (EAS) were evaluated on epilepsy models. Methods: Pentylenetetrazole (PTZ), pilocarpine, and maximal electroshock (MES)-induced convulsions in mice were recorded. EAS (100, 200, and 300 mg/kg, p.o.) protected of mice against PTZ, pilocarpine, and MES-induced seizures, respectively. Results: In MES-induced seizures, the results revealed that EAS decreased the duration of the tonic hindlimb extension and percent mortality. In addition, these doses of EAS increased the latency for the development of convulsions and reduced mortality in mice against PTZ and pilocarpineinduced convulsions. Conclusion: The ethanolic extract of bark A. scholaris exhibited anticonvulsant potential in various animal models. Keywords: Alstonia scholaris, Pentylenetetrazole, Pilocarpine, Maximal electroshock, Anticonvulsant effect.